Competition authority in a trap? A few (bitter) words on making public policy by counteracting an unfair use of a contractual advantage in agri-food sector in Poland - Agata Jurkowska-Gomułka (Central European Public Administration Review)
A problem of counteracting bargaining powers of retailers, specially in agri-food sector, has been recently addressed by regulations in a few European countries but so far it has not been subject to academic considerations. A paper aims at finding rationales of granting administrative bodies with competences of interfering in contractual relationships between market players in reference to an abuse or misuse of bargaining power and to assess a possibility and probability of balancing public and private interests by administrative bodies applying regulations on counteracting an unfair use of a bargaining power. A point of reference for considerations is a Polish regulation dated from December 2016 - Act on Counteracting the Unfair Use of Contractual Advantage in the Trade in Agricultural and Food Products. In a lack of relevant case law a paper is based on a descriptive method of research as well as a method of conceptual analysis. A paper contests a correctness and rationality of selecting a competition authority as an enforcer of a discussed regulation. A competition authority seems to be caught in a trap of opposite (public and private) interests - an antitrust authority shall undertake an intervention in an interest of a private entity which in many situations may be seen as an intervention against public interest. A paper contributes to an ongoing discussion on EU's proposals for actions on eliminating imbalances between big retailing networks and food suppliers.